PENGEMBANGAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) BERBANTU VIDEO CAMTASIA PADA MATERI PELUANG UNTUK SISWA SMA/MA NEGERI KABUPATEN CILACAP TAHUN PELAJARAN 2013/2014 - Retno, Eli Widoyo; Mardiyana, Mardiyana; Kusmayadi, Tri Atmojo (Jurnal Pembelajaran Matematika, 2014)
Abstract. The objectives of this research were to investigate: (1) the process and result of the development of the GI learning model; (2) the effectiveness of the modified GI learning model toward the studentsâ learning achievement in Mathematics and character of social responsibility in the topic of discussion of Probability. This research used the Research and Development (R&D) method. It consisted of two phases, namely: (1) research and development phase and (2) effectiveness test phase of the modified GI learning model. The former, with some modifications, referred to the ones claimed by Borg and Gall. The latter used the quasi experimental research method. The results of the research were as follows: 1) The modified GI learning model assisted with Camtasia Video is a valid, effective, and practical learning model. In addition, it also matches 2013 curriculum so that it was applicable in Senior Secondary Schools/Islamic Senior Secondary Schools of Cilacap. 2) The modified GI learning model assisted with Camtasia Video is more effective than the GI learning model toward the studentsâ learning achievement in Mathematics and the character of social responsibility on the topic of discussion of Probability.Â Keywords: Learning model, GI, Camtasia Video, Learning achievement, and Social responsibility